Dialogo adresantas ir adresatas - Vilkienė, Loreta (Kalbotyra, 1998)
One of the distinctive features of dialogue, when compared with the monologue, is the categories of the addresser and the addressee. The addresser is considered to be the person who creates the message while the person to whom this message is addressed is thought to be the addressee. It is typical to the dialogue that its content and meaning appear as the derivative of the contents created by both partners of communication. The addresser as well as the addressee may be individuals or groups of individuals. The partners of communication should understand not only utterances but also apprehend some extralinguistic matters, for instance, context, evaluate partner’s presupposition, imagine partner’s communicative portrait which may alter and change the content and form of the dialogue during the conversation. The chosen model of transactive and interactive communication conditions the linguistic behaviour of the addresser and the addressee.